2018
DOI: 10.24938/kutfd.372255
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Scube1 in Patients Presenting to the Emergency Department Due to Angina Pectoris

Abstract: Objective: The purpose of this study was to investigate the value of signal peptide-CUB-EGF domain-containing protein 1 (SCUBE1) in the diagnosis of angina pectoris in patients presenting to the emergency department. Sonuç: Çalışmamızın bulgularına göre SCUBE 1, iskemik göğüs ağrısı etiyolojilerinin tanısında değeri bulunmamaktadır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addiditon they found that serum triglyceride levels increased but glucose levels decreased in the obese group and both triglyceride and glucose levels exhibited no significant difference between the control and obese groups 28 . Dai et al observed that plasma SCUBE1 levels were higher in cases of acute coronary syndrome and acute ischemic stroke compared to the control group, whereas Şahin et al did not identify a statistically significant correlation 29,30 . In the current study, we found that SCUBE 1, triglyceride and glucose levels were higher in obese and DM rats.…”
Section: Discussionmentioning
confidence: 97%
“…In addiditon they found that serum triglyceride levels increased but glucose levels decreased in the obese group and both triglyceride and glucose levels exhibited no significant difference between the control and obese groups 28 . Dai et al observed that plasma SCUBE1 levels were higher in cases of acute coronary syndrome and acute ischemic stroke compared to the control group, whereas Şahin et al did not identify a statistically significant correlation 29,30 . In the current study, we found that SCUBE 1, triglyceride and glucose levels were higher in obese and DM rats.…”
Section: Discussionmentioning
confidence: 97%